2012
DOI: 10.1021/es300983r
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Bayesian Network for Studying the Causal Links between Phosphorus Loading and Plankton Patterns in Lake Simcoe, Ontario, Canada

Abstract: An ecosystem perspective to restoring beneficial uses in Areas of Concern can be interpreted as a shift from the traditional elucidation of simple cause-effect relationships to a multicausal way of thinking that more effectively accommodates ecosystem complexity. This holistic management paradigm has also pervaded the contemporary ecological modeling practice, making compelling the adoption of more sophisticated ecosystem modeling tools. In this study, our primary objective is to develop a Bayesian hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 26 publications
1
33
1
Order By: Relevance
“…Human activities increased external loads, which have accelerated the eutrophication process and triggered internal nutrient loading processes (Reddy et al 1998). As a result, internal loading can delay (Gudimov et al 2012) recovery of water quality even after the external nutrient load has decreased. Before taking actions to deal with eutrophication, much preliminary work needs to be done (Zamparas and Zacharias 2014), including monitoring all the potential nutrient sources (e.g., external nutrient loading and internal nutrient loading).…”
Section: Comparison With Other Regionsmentioning
confidence: 99%
“…Human activities increased external loads, which have accelerated the eutrophication process and triggered internal nutrient loading processes (Reddy et al 1998). As a result, internal loading can delay (Gudimov et al 2012) recovery of water quality even after the external nutrient load has decreased. Before taking actions to deal with eutrophication, much preliminary work needs to be done (Zamparas and Zacharias 2014), including monitoring all the potential nutrient sources (e.g., external nutrient loading and internal nutrient loading).…”
Section: Comparison With Other Regionsmentioning
confidence: 99%
“…One of the most criticized issues with deterministic models is the use of parameters that cannot be unambiguously determined (Gudimov et al 2012) and the way models are calibrated by tuning these parameters until the model simulations fit the observations Beets 1994, Rykiel 1996). This is not considered correct, because different sets of parameters can yield a similar outcome.…”
Section: Different Approaches To Modelling Phytoplanktonmentioning
confidence: 99%
“…Still, it has received quite limited attention among aquatic modellers; for the review it was possible to identify only 13 fairly recent papers that introduced a SEM application for phytoplankton studies. In most of those the impact of different biotic and abiotic variables on phytoplankton development and on the phytoplankton community were examined (Arhonditsis et al 2006, 2007a, b, Liu et al 2010, Salmaso 2011, Gudimov et al 2012 and especially in biodiversity studies the regional and latitudinal effect was included (Korhonen et al 2011, Stomp et al 2011, Chou et al 2012, Matthews and Pomati, 2012. In this study SEM was used to examine the factors affecting the development of phytoplankton in Lake Valkea-Kotinen.…”
Section: Structural Equation Modelling (Ii Iii)mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the modelled range of the monthly TP concentrations was much narrower than the actual values and the predicted patterns failed to reproduce the substantial inter-annual variability characterizing the system . In Lake Simcoe, Gudimov et al (2012) recently introduced a spatially-explicit simple mass-balance model forced with idealized sinusoidal loading to predict total P concentrations. The study reported two-fold discrepancy between empirical gross and predicted net TP sedimentation rates, presumably reflecting the role of macrophytes and dreissenids, the sediment resuspension induced by wind forcing, the diffusive release of P from the sediments, and the complex interplay between offshore waters and the two embayments of Lake Simcoe (Cook's Bay and Kempenfelt Bay).…”
Section: Introductionmentioning
confidence: 99%